Co-curricular management practices among novice teachers in Malaysia - Hussin, Fauzi; Don, Yahya; Omar Fauzee, Mohd Sofian; Daud, Yaakob; Raman, Arumugan; H.A. , Ismail; Hj. Yaakub, Muhamadul Bakir (GNU General Public License, 2014)
This article aims to identify the level of knowledge and preparedness among novice teachers in the implementation of co-curricular activities in secondary schools in the state of Kedah, Malaysia. A total of 162 novice teachers deployed to teach in secondary schools throughout the state of Kedah answered the questionnaire completely. The data were analyzed using descriptive statistics and statistical inference including mean, percentage, independent samples t-test, ANOVA and Pearson correlation. The results, based on six different academic disciplines, show that novice teachers in the humanities, sciences and technical were higher than novice teachers of language areas in the level of knowledge in managing as well as their willingness to plan teaching and learning co-curricular activities in school. A comparison of novice teachers based on gender showed that there was no significant difference between male and female teachers related to level of knowledge and preparedness in managing co-curricular activities. The Pearson correlation analysis showed positive and significant correlation between teachers' readiness in planning teaching and learning and the teachers’ knowledge in managing co-curricular activities. Furthermore, novice teachers who had attended the extra-curricular course during the first degree acquired higher levels of knowledge in managing extra-curricular activities after teaching in schools.